Bioactive Compounds and Antioxidant Activity of Lettuce Grown in Different Mixtures of Monogastric-Based Manure With Lunar and Martian Soils - Duri, Luigi G.; Pannico, Antonio; Petropoulos, Spyridon A.; Caporale, Antonio G.; Adamo, Paola; Graziani, Giulia; Ritieni, Alberto; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Nutrition, 2022)
The supplementation of bioactive compounds in astronaut's diets is undeniable, especially in an extreme and inhospitable habitat of future space settlements. The aim of this study was to enhance the Martian and Lunar regolith fertility (testing two commercial simulants) through the provision of organic matter (manure) as established by in situ resource utilization (ISRU) approach. In this perspective, we obtained 8 different substrates after mixing Mojave Mars Simulant (MMS-1) or Lunar Highlands Simulant (LHS-1), with four different rates of manure (0, 10, 30 and 50%, w/w) from monogastric animals. Then we assessed how these substrates can modulate fresh yield, organic acids, carotenoids content, antioxidant activity, and phenolic profile of lettuce plants (Lactuca sativa L.). Regarding fresh biomass production, MMS-1-amended substrates recorded higher yields than LHS-1-ones; plants grown on 70:30 MMS-1/manure mixture produced the highest foliar biomass. Moreover, we found an increase in lutein and β-carotene content by +181% and +263%, respectively, when applying the highest percentage of manure (50%) compared with pure simulants or less-amended mixtures. The 50:50 MMS-1/manure treatment also contained the highest amounts of individual and total organic acids, especially malate content. The highest antioxidant activity for ABTS assay was recorded when no manure was added. The highest content of total hydroxycinammic acids was observed when no manure was added, while ferulic acid content (most abundant compound) was the highest in 70:30 simulant/manure treatment, as well as in pure LHS-1 simulant. The flavonoids content was the highest in pure-simulant treatment (for most of compounds), resulting in the highest total flavonoids and total phenols content. Our findings indicate that the addition of manure at specific rates (30%) may increase the biomass production of lettuce plants cultivated in MMS-1 simulant, while phytochemical composition is variably affected by manure addition, depending on the simulant. Therefore, the agronomic practice of manure amendment showed promising results, however it must be tested with other species or in combination with other factors such as fertilization rates or biostimulants application to verify its applicability in space colonies for food production purposes.